Analysis of Pavement Damage Types on Provincial Roads in the Madura Region - Kurniawan, Adi; Patriadi, Andi; Sajiyo, Sajiyo (Transpublika Publisher, 2025)
Roads play a crucial role in fostering economic development and facilitating transportation within communities. However, in the Madura region, issues such as cracks, potholes, and raveling are frequently observed, posing challenges to road quality and safety. This study aims to investigate the prevalent types of road defects in this area in order to inform better infrastructure planning and management. To achieve this objective, the research focused on provincial roads in the Madura region, utilizing a combination of field surveys and questionnaires with road users in Pamekasan. The findings of the study highlighted cracks, potholes, and grain detachment as the most commonly observed forms of road damage in the region. These results are essential for guiding decision-making processes related to road maintenance and repair, ultimately enhancing the efficiency and quality of road infrastructure. The insights gained from this study offer valuable guidance for policymakers and stakeholders involved in road infrastructure development. Recommendations arising from the research include prioritizing the management of road damage, ensuring adequate budget allocation for repairs, and implementing regular maintenance practices to prevent deterioration.